A települési kötédés és a z generáció - egy magyarországi középváros példája (The Settlement Engagement and the Z Generation – the Example of a Hungarian City) - Nikoletta Tóth-Kaszás (DETUROPE)
My research focuses on the settlement aspects of nonbusiness marketing. It highlights a problem, which today many domestic and rural communities are struggling with: the out-migration of young people. This long-lasting problem in the rural environment has continued in the 2010s and affects not only villages, small towns but mid-sized cities, as well. Many research results indicate that retention of a young workforce is a generic problem in Hungary today, almost in every settlement. In this paper I highlight the different approaches of identity and also the values that are important to the high school students, as the members of generation Z. I also analysed their bondage to the settlement where they live. I take the case of a Hungarian mid-sized city. The purpose of this study is to explore the strength of the urban attachment of the young people and the way how they see the city. Doing this, my goal is to show the direction of further development of the settlement, and thus, in the broader sense, the future development of Hungarian towns and mid-sized cities as well. Kutatásom a nonbusiness marketing települési aspektusait vizsgálja. Azon problémát állítja középpontba, amellyel napjainkban számos hazai, vidéki település küzd: a fiatalok elvándorlását. Ez a vidéki környezetet régóta sújtó probléma a 2010-es években tovább gyűrűzött, s immár nem csak a falvakat, kisvárosokat, de a vidéki nagyvárosokat is érinti. Számos kutatás eredménye jelzi, hogy a fiatal munkaerő megtartása generális problémát jelent ma Magyarországon, szinte minden település számára. Jelen tanulmányban rávilágítok az identitás különböző megközelítéseire, továbbá arra, hogy a jelenleg középiskolás fiatalok, vagyis a Z generáció mit tartanak értéknek, kötődnek-e a településhez, ahol élnek. A vizsgálathoz egy magyarországi középváros esetét veszem alapul. A tanulmány célja, hogy feltárja a fiatalok városi kötődésének erősségét, továbbá azt, hogy milyennek látják a várost jelenleg. Mindezzel célom, hogy irányt mutassak a település további fejlődéséhez, ezáltal pedig tágabb értelemben a magyar kis- és középvárosoknak egyaránt.